2017
DOI: 10.4041/kjod.2017.47.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a new type of clear overlay retainer on occlusal contacts

Abstract: The popularity of clear overlay retainers (CORs) has increased recently because of their advantages such as better esthetics, cost effectiveness, easy fabrication, and good compliance. However, a deficiency in posterior occlusal settling is a reported limitation of CORs. The aim of this study was to evaluate the posterior occlusal contact changes in a new type of clear orthodontic retainer called Oral-treaper (OTP), which consists of three layers and has stronger mechanical characteristics than do conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
1
7
0
2
Order By: Relevance
“…The increase in posterior force might be due to a vertical settling effect. This result might support our previous study, which showed the post-orthodontic settling in OTP with cast models [ 8 ]. Although all the incisal edges and occlusal surfaces were covered with removable retainers, the change of occlusion under retention period with OTP was different from that with VFR.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The increase in posterior force might be due to a vertical settling effect. This result might support our previous study, which showed the post-orthodontic settling in OTP with cast models [ 8 ]. Although all the incisal edges and occlusal surfaces were covered with removable retainers, the change of occlusion under retention period with OTP was different from that with VFR.…”
Section: Discussionsupporting
confidence: 92%
“…Two weeks later, they received an Oral-Treaper (OTP) retainer for the maxillary dentition and a tongue elevator for the mandibular dentition ( Figure 4 ). As described above, the OTP is a clear-overlay type retainer which is composed of three layers ( Figure 1 ) [ 7 , 8 ]. The outer layer is polyethylene terephthalate glycol (PETG), the middle layer is thermoplastic polyurethane (TPU), and an inner layer is a reinforced resin core.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, core integration contributes to the dimensional stability. The lateral wall of the appliance is well maintained without distortion or expansion, and thus, the arch width can be stabilized [ 45 ]. This may be the reason for the low force distribution of model 3 in our study.…”
Section: Discussionmentioning
confidence: 99%